The role of NGOs in protecting the environment from the point of view of their employees (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The current research started from a field study on the role of NGOs in protecting the environment from the viewpoint of their employees. The Youth Society for Environmental Protection and Pollution Control and the Syrian Coast Society in Lattakia were selected as a model, as it aimed to identify the role of NGOs in protecting the environment in the following areas: (Cognitive, skill, and emotional) as well as identifying the differences in this role according to the following variables: (educational status, number of years of experience). Statistical treatments were used that are proportional to the research formula and what is desired by the application, including (internal consistency, tool stability, arithmetic mean, Pearson correlation coefficient, and Spearman-Brown coefficient).  The Syrian coast and the sample amounted to (68) items. The research showed several results according to the variables presented, and the presence of significant and essential differences between the answers of the research sample members according to the educational status variable, as well as the variable number of years of experience.